E-learning berbasis AIKIDS pada Pembelajaran Koding untuk Siswa Jenjang Sekolah Dasar - Ardani, Ardani; Setiawan, Arif (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
The use of technology in education can improve the quality of learning and student involvement in the learning process. However, the use of technology, especially smartphones, among elementary school students has not been utilized properly, because they are only used for entertainment and playing games. This can interfere with concentration and reduce the time students spend studying on computer extracurriculars. So interactive learning media is needed to attract students' interest in learning. This research aims to develop AIKIDS-based E-learning in interactive coding learning and determine the feasibility level of E-learning. The research method used is Research and Development (R&D) with a Define, Design, Develop, Disseminate (4D) development model. Data collection methods are interviews and questionnaires, then data analysis is carried out with percentages based on the level of media suitability which will be converted to a suitability scale. This research produces an AIKIDS-based E-learning product for coding learning for elementary schools. The first test results from two media experts obtained results of 85% and were included in the very feasible category. The second test carried out by material experts obtained results of 93%, including the very feasible category. The third test was carried out with 20 students using the System Usability Scale (SUS) test, getting an average result of 91 which was included in the "Excellence" category or the same as scale B.